Human Development by Gender and National Culture: A Comparative Analysis - Pereira Sartori Falguera, Fernanda [UNESP]; Lima, M. A.N.U.E.L.L.A.A.F. [UNESP]; Ferrari, Vanessa A. S. [UNESP]; Barriga, Gladys D. C. [UNESP]; Mariano, Enzo B. [UNESP] (Taylor & Francis, 2021)
The differences between female and male human development indicators are evidence that the general scenario (whole population) presents a blurred analytical viewpoint. Female schooling and life expectancy have advanced, but income is far from keeping pace. For women, legislation does not seem to be enough without the cultural legitimisation; for men, the cultural dependency on psychopathologies derived from the subjective expectations of masculinity is more evident. However, no study has apparently analysed the influence of national culture (NC) on human development (HD), by comparing the General, Female, and Male scenarios. This research sought to fill this gap by applying univariate and multivariate techniques to the data from 59 countries, using the Hofstede cultural dimensions as independent variables, HD indicators as dependent variables, and democracy, agricultural dependence, and urbanisation as controls. The influence of culture is a reality in all scenarios, but differs according to gender. For women, individualism appears to be a more powerful ally, and masculinity and uncertainty avoidance more harmful factors than for men; for men, power distance and indulgence have a greater impact than on women. Considering HD as a whole, an autonomous thinking society that rejects unjustifiable inequalities seems to be the most important cultural enabler.